2014
DOI: 10.1038/cddis.2014.272
|View full text |Cite
|
Sign up to set email alerts
|

Dysferlin regulates cell membrane repair by facilitating injury-triggered acid sphingomyelinase secretion

Abstract: Dysferlin deficiency compromises the repair of injured muscle, but the underlying cellular mechanism remains elusive. To study this phenomenon, we have developed mouse and human myoblast models for dysferlinopathy. These dysferlinopathic myoblasts undergo normal differentiation but have a deficit in their ability to repair focal injury to their cell membrane. Imaging cells undergoing repair showed that dysferlin-deficit decreased the number of lysosomes present at the cell membrane, resulting in a delay and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(130 citation statements)
references
References 58 publications
7
121
0
1
Order By: Relevance
“…Direct Ca 2+ entry by focal cell membrane injury by a pulsed laser caused an instantaneous rise in [Ca 2+ ] c , which decreased over the next minute as the cell repaired ( Figure 1c). 16 Calcium ionophore (ionomycin) caused rapid and sustained increase in [Ca 2+ ] c ( Figure 1d). The amplitude of [Ca 2+ ] c increase by injury or ionomycin was twice as large as the receptor-mediated signaling ( Figure 1e).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Direct Ca 2+ entry by focal cell membrane injury by a pulsed laser caused an instantaneous rise in [Ca 2+ ] c , which decreased over the next minute as the cell repaired ( Figure 1c). 16 Calcium ionophore (ionomycin) caused rapid and sustained increase in [Ca 2+ ] c ( Figure 1d). The amplitude of [Ca 2+ ] c increase by injury or ionomycin was twice as large as the receptor-mediated signaling ( Figure 1e).…”
Section: Resultsmentioning
confidence: 98%
“…60,61 We have identified that injury-triggered lysosome exocytosis causes secretion of acid sphingomyelinase (ASM), which is needed for cell membrane repair. 16 ASM secretion by glial cells is also triggered by ATP, which in turn regulates secretion of inflammatory cytokines. 57 Thus, by releasing ASM and ATP in response to injury, lysosome exocytosis can coordinate repair of brain injury at both the cellular and tissue levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Cells from NPA patients, lacking ASMase protein, or Limb Girdle Muscular dystrophy 2B (LGMD2B) patients (lacking dysferlin protein), who show slow and poor injurytriggered ASMase secretion both show compromised PMR. 4,23 The PM repair deficit in these patient cells can be rescued by providing sphingomyelinase. 4 ASMase is also known to trigger cell membrane shedding and could contribute to the shedding of membrane by ectocytosis.…”
Section: The Membrane Repair Machinerymentioning
confidence: 99%
“…Muscle and lung cells offer a good example of this as they are routinely wounded as a result of exercise and over stretching. 1,2 Defect in the muscle cell's ability to repair has been shown to result in muscular dystrophy, [3][4][5][6] where poor repair of injured muscle cell membrane leads to cell death and tissue inflammation. Poor plasma membrane repair (PMR) is also associated with NiemannPick type A, 7 diabetes, 8 and ChediakHigashi 9 syndrome and therapies targeting PMR have been shown to be effective in treating muscle and lung injuries.…”
Section: Introductionmentioning
confidence: 99%